Centennial : Disc 2 - Wilder, John, 1934-; Conrad, Robert, 1935-2020.; Chamberlain, Richard, 1935-; Burr, Raymond, 1917-1993.; Kellerman, Sally; Carrera, Barbara; Harrison, Gregory, 1950-; Zimbalist, Stephanie; Raines, Cristina, 1952-; Crenna, Richard, 1927-2003.; Karras, Alex.; De Young, Cliff; et al. (Universal City, California Universal Studios Home Entertainment, 2008)
Relive the grand hopes, dreams, loves and adventures of generations of residents in Centennial, Colorado-- from their risky attempts to establish a settlement in 1795 through the politics and power plays of the 20th century.
Disc 2: Chapter 3: The wagon and the elephant / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Jerry Ziegman ; directed by Paul Krasny -- Chapter 4: For as long as the waters flow / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Jerry Ziegman ; directed by Paul Krasny. Disc 1: Chapter 1: Only the rocks live forever / produced by Howard Alston ; written for television by John Wilder ; directed by Virgil W. Vogel -- Chapter 2: The yellow apron / produced by Howard Alston ; written for television by John Wilder ; directed by Virgil W. Vogel. Disc 3: Chapter 5: The massacre / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Charles Larson ; directed by Paul Krasny -- Chapter 6: The Longhorns / produced by Alex Beaton ; written for television by John Wilder ; directed by Virgil W. Vogel. Disc 4: Chapter 7: The shepherds / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Charles Larson ; directed by Virgil W. Vogel -- Chapter 8: The storm / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Charles Larson ; directed by Harry Falk. Disc 5: Chapter 9: The crime / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Charles Larson ; directed by Harry Falk -- Chapter 10: The winds of fortune / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Charles Larson ; directed by Harry Falk. Disc 6: Chapter 11: The winds of death / developed for television by John Wilder ; produced by Malcolm R. Harding ; teleplay by Jerry Ziegman ; directed by Bernard McEveety -- Chapter 12: The scream of eagles / produced by George E. Crosby ; written for television by John Wilder ; directed by Virgil W. Vogel.
Title from container.
Based on the novel by James Michener.
Originally broadcast on television in 1978.
Contains all 2 episodes from the television mini-series.
Special feature: "Memories of 'Centennial'."
Robert Conrad, Richard Chamberlain, Raymond Burr, Sally Kellerman, Barbara Carrera, Gregory Harrison, Stephanie Zimbalist, Cristina Raines, Richard Crenna, Alex Karras, Cliff De Young, Dennis Weaver, Glynn Turman, Rafael Campos, Robby Weaver, Timothy Dalton, Lynn Redgrave, Brian Keith, Clive Revill, Anthony Zerbe, Lois Nettleton, Doug McKeon, William Atherton, Jesse Vint, David Janssen, Robert Vaughn, Andy Griffith, Sharon Gless, Merle Haggard.
Keywords: Michener, James A. -- 1907-1997 -- Film adaptations; Frontier and pioneer life -- Colorado -- Drama; Film adaptations; Cities and towns; Closed captioning; Drama. -- Colorado; Colorado -- Social life and customs -- Drama; Colorado -- History -- To 1876 -- Drama; Colorado -- History -- 1951- -- Drama; Colorado -- Politics and government -- To 1876 -- Drama; Colorado -- Politics and government -- 1951- -- Drama; Colorado; DVD-Video discs; video recordings (physical artifacts); Drama; Television adaptations; Television mini-series; Television programs; Television programs for the hearing impaired; Video recordings for the hearing impaired; Television mini-series.; Historical television programs; Western television programs; Action and adventure television programs; Historical drama; Film adaptations